Measuring implicit intergroup biases. Issue 1 (4th November 2020) - Lai, Calvin K.; Wilson, Megan E.
Abstract: Implicit intergroup biases are automatically activated prejudices and stereotypes that may influence judgments of others on the basis of group membership. We review evidence on the measurement of implicit intergroup biases, finding: implicit intergroup biases reflect the personal and the cultural, implicit measures vary in reliability and validity, and implicit measures vary greatly in their prediction of explicit and behavioral outcomes due to theoretical and methodological moderators. We then discuss three challenges to the application of implicit intergroup biases to real‐world problems: (1) a lack of research on social groups of scientific and public interest, (2) developing implicit measures with diagnostic capabilities, and (3) resolving ongoing ambiguities in the relationship between implicit bias and behavior. Making progress on these issues will clarify the role of implicit intergroup biases in perpetuating inequality.